Devotion. - Smith, Patti (Why I write, 2017)
"Devotion is short enough to devour at one enjoyable sitting and thought-provoking enough to deserve re-reading."-Suzi Feay, Financial Times "Devotion shows rather than tells what it means to give a life to writing."-Katherine Cooper, Hyperallergic A work of creative brilliance may seem like magic-its source a mystery, its impact unexpectedly stirring. How does an artist accomplish such an achievement, connecting deeply with an audience never met? In this groundbreaking book, one of our culture's beloved artists offers a detailed account of her own creative process, inspirations, and unexpected connections. Patti Smith, a National Book Award-winning author, first presents an original and beautifully crafted tale of obsession-a young skater who lives for her art, a possessive collector who ruthlessly seeks his prize, a relationship forged of need both craven and exalted. She then takes us on a second journey, exploring the sources of her story. We travel through the South of France to Camus's house, and visit the garden of the great publisher Gallimard where the ghosts of Mishima, Nabokov, and Genet mingle. Smith tracks down Simone Weil's grave in a lonely cemetery, hours from London, and winds through the nameless Paris streets of Patrick Modiano's novels. Whether writing in a café or a train, Smith generously opens her notebooks and lets us glimpse the alchemy of her art and craft in this arresting and original book on writing. The Why I Write series is based on the Windham-Campbell Lectures, delivered annually to commemorate the awarding of the Donald Windham-Sandy M. Campbell Literature Prizes at Yale University.